A MOTHER'S EXPERIENCE OF FACING THE DIAGNOSIS OF PALLISTER KILLIAN SYNDROME - Kuder Anja; Žgur Erna (Innovative Issues and Approaches in Social Sciences, 2024)
Pallister Killian syndrome is a rare genetic disease, the 12p chromosome is defective. People with Pallister Killian syndrome have problems in all areas of functioning. Intellectual deficits and associated diseases are common. Just as the deficits are permanent, so is the help that a person with Pallister Killian syndrome will need throughout life. Informing the parents about the diagnosis often means giving them less favourable news. Parents receive information about the diagnosis from medical professionals, and then they have to familiarise themselves with the disease, confront it and live with it. The article presents how a girl's mother coped with the diagnosis of Pallister Killian syndrome, who offered her the most support and what she missed the most in the process of coping with the diagnosis. The research found that in this early period, systemic support from various health service and treatment providers, as well as help in asserting the rights she was entitled to due to her child's diagnosis, were most missed by the mother.